Intraosseous ganglion cyst of the lunate: A case report - Sbai, Mohamed Ali (Chin J Traumatol, 2016)
Intraosseous ganglion cyst of the carpal bones represents a rare cause of wrist pain. We report a case of a 42 year-old, right-handed female, who presented with pain of the right wrist following a fall on the palm of the hand. Clinical study revealed a moderate swelling over the mid-section of the palmar face and pain through extreme ranges of motion of the wrist. Plain radiographs and CT-scan of the wrist have revealed an intraosseous ganglion cyst of the lunate bone. Curetting-filling by Kuhlman's vascularized radial bone graft allowed a good functional recovery. The clinical, radiological and therapeutic aspects are discussed.